TOURISM AS A TOOL FOR SOCIO-ECONOMIC DEVELOPMENT OF ISSYK-KUL REGION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article considers the state of development of the tourism industry in the IssykKul region and its impact on the socio-economic indicators of the region. A statistical analysis of the arrivals of tourists in the region was carried out, the tourist and recreational resources of the region are recorded. Election of the main problems of tourism development in the tourism sector, such as greening the economy, improvement, employment, attracting investment, improving the regulatory framework for tourism development in the health sector.The strategic tasks of the state to create an environment favorable for human life by preserving the unique natural ecosystems of the Issyk-Kul region and the rational use of natural resources are considered. Hotels and guest houses, catering establishments, travel agencies of the Issyk-Kul region, the Karakol ski base and other freeride bases (Jyrgalan, Boz-Uchuk, Altyn-Arashan) were studied. The potential of the airports «Tamchy», «Karakol» was considered. The reconstruction of the Karakol airport also contributes to the improvement of the socio-economic development of the region. The development of the tourism sector is based on a cluster approach. The problems of sustainable development of tourism are considered. Based on the SWOT analysis, the main problems are identified and recommendations are given that can contribute to the improvement of socio-economic indicators and the development of the tourism industry in the Issyk-Kul region.
Keywords: tourism sector, socio-economic development, tourism development, cluster, economic indicators, green tourism, green economy, regional tourism, freeride